2022
DOI: 10.24966/escr-5020/100037
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Variation in Soil Microbial Population and Associated Soil Properties in Long Term Soil Fertility

Abstract: The purpose of this research was to analyze soil samples from different altitudes of Nepal to know about their physical, chemical and biological properties; including the content of N, P, K, O, C, pH and population of bacteria, fungus and Azotobacter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The result of this study showed that the higher population of Azotobacter found in lower altitude in coffee arabica rhizosphere in Bener Meriah Regency. This condition as same as with [17] that maintainance of Azotobacter in higher altitude is very important so we can to sustain food production. The higher altitudes is higly influenced to physiochemical properties of soil ecosystems.…”
Section: Population Of Azotobacter At Different Altitude In Arabica C...mentioning
confidence: 55%
“…The result of this study showed that the higher population of Azotobacter found in lower altitude in coffee arabica rhizosphere in Bener Meriah Regency. This condition as same as with [17] that maintainance of Azotobacter in higher altitude is very important so we can to sustain food production. The higher altitudes is higly influenced to physiochemical properties of soil ecosystems.…”
Section: Population Of Azotobacter At Different Altitude In Arabica C...mentioning
confidence: 55%